New Challenges for Health Systems of the European Union - Boruzs, Klára; Bányai, Gábor; Bíró, Klára (International Journal of Engineering and Management Sciences, 2016)
The health system is facing a number of difficultiesnot only in our country, but in the whole of Europe. In the 21st century never before seenlarge-scale problems pose a serious threat to our world, which have a significant impact on health care. We outline the challenges of today and examine their likely effect on coming health policies.